Use of implementation science to plan adoption of a tobacco-free policy on a historically black college/university (HBCU) campus. - Selove, Rebecca; Aghili, Mahnaz; Green, Cheryl; Brown, Charles (Journal of American College Health, 2022)
Objective: Implementation science tools were used to identify facilitators and barriers to adopting a tobacco-free policy on a historically Black college/university (HBCU). Participants: Study participants included 13 University staff, two students, and two public health educators/school alumni. Data were collected in 2015–2016. Methods: The Consolidated Framework for Implementation Research (CFIR) was used to develop questions for focus groups and individual interviews. The CFIR was also used by two research team members to code transcripts independently, using an iterative deduction process to achieve ≥85% agreement on CFIR domains. Coded quotations were evaluated using the Qualitative Implementation Framework (QIF) to ascertain next adoption planning steps. Results: Qualitative data suggested that building capacity for tobacco control, linking policy to HBCU identity and priorities such as addressing marijuana use might facilitate adoption of a tobacco-free campus policy. Conclusions: Implementation science tools may be useful for planning adoption of comprehensive tobacco-free policies at HBCUs.